Strategi Pemerintah Daerah Dalam Menangani Pernikahan Dini di Kecamatan Sinjai Selatan Kabupaten Sinjai - Anugrah, Dian; Muhiddin, Amir; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2020)
This study purposed to find out the strategy of the local government in dealing with early marriage in South Sinjai District, Sinjai Regency. This study used qualitative research, data sources were primary and secondary, the number of informants was 9 people. Data collection used observation, interview and documentation. The results of this study showed that the strategy of the local government in dealing with early marriage in south Sinjai District Sinjai Regency was classified as optimal and not optimal when discussed from the aspect of (1) socialization, had been running according to the existing theory, but not yet optimal because there were still obstacles and obstacles from some communities; (2) regulations, related to regulations regarding marriages had been implemented well, but not yet optimal due to the government's lack of clarity on people who get married early; (3) sanctions, the application of sanctions against early marriage had proceeded relatively well. Internal factors that influence in this research were on their own volition. While external factors were influenced by several factors such as economics, education, or community traditions.